Main tendencies in applied materials science : selected, peer reviewed papers from the 28th Regional Conference on Solid State Science and Technology 2014 (RCSSST 2014), November 25-27, 2014, Cameron Highlands, Pahang, Malaysia - Azhan, H. (Materials science forum ;, 2016)
Methods of synthesis, processing and analysis of different materials, advanced approaches in modern Materials Science and industrial technology.Methods of Solid-state science for application in different areas of materials research.